High energy storage density and discharging efficiency in La3+/Nb5+-co-substituted (Bi0.5Na0.5)0.94Ba0.06TiO3 ceramics. Issue 10 (August 2019) - Yang, Yang; Wang, Hua; Bi, Linnan; Zheng, Qiaoji; Fan, Guifen; Jie, Wenjing; Lin, Dunmin
Abstract: In this work, [(Bi1- x La x )0.5 Na0.5 ]0.94 Ba0.06 (Ti1-5y/4 Nby )O3 ceramics have been developed by the dual-substitution of La 3+ for Bi 3+ and Nb 5+ for Ti 4+ and prepared by an ordinary sintering technique. All ceramics can be well-sintered at 1200 °C. The addition of La 3+ and Nb 5+ reduces the grain size and improve the dielectric breakdown strength of the ceramics; moreover, after the introduction of La 3+ and Nb 5+, the remanent polarization of the ceramics is significantly reduced, while the maximum polarization remains the same large value as that of the ceramic without the doping of La 3+ and Nb 5+ . As a result, high energy storage density and discharge efficiency are achieved at x /y = 0.07/0.02, giving the large storage density of 1.83 J/cm 3 and high discharging efficiency of 70%. The present work presents a feasible strategy to develop energy storage materials based on perovskite ferroelectrics by the partial substitutions in the A and B sites.